Strengthening Investment Climate: A Study of Dynamic Governance in Gorontalo Province - Rahmat Kokalo, Milawaty; Aneta, Asna; M. Wantu, Fence; Aneta, Yanti (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
This study aims to analyze the implementation of Dynamic Governance in investment policies in Gorontalo Province. it emphasizes flexibility, innovation, and adaptability in the decision-making process, so that it can respond to changes in the investment environment more effectively. In the context investment policies, they still face various challenges, including regulations that are not yet fully adaptive, complex bureaucracy, and limited infrastructure that can hinder investment attractiveness. The research method used is a qualitative approach with data collection techniques through in-depth interviews, documentation studies, and direct observation of policies implemented by the Investment and One-Stop Integrated Service Office (DPMPTSP). The results of the study indicate that efforts to digitize licensing services and bureaucratic reform have been carried out, but have not been fully optimal in creating a conducive investment environment. In addition, the lack of coordination between local and central governments is often an obstacle to effective policy implementation. With a more adaptive and innovative strategy, it is hoped that Gorontalo can increase its competitiveness as an attractive and sustainable investment destination